Overcoming Challenges on an International Project to Advance Systems Engineering. Issue 3 (12th November 2019) - Davidz, Heidi; Ferris, T.L.J.; Henry, Devanandham; Hilburn, Thomas B.; Hutchison, Nicole A.C.; Olwell, David H.; Prun, Daniel; Pyster, Art; Roussel, Jean‐Claude; Sillitto, Hillary; Snoderly, John; Squires, Alice F.; et al.
ABSTRACT: The Body of Knowledge and Curriculum to Advance Systems Engineering (BKCASE) project's dual product development cycle spanned a three‐year period from the September 2009 to December, 2012. During this timeframe, BKCASE authors met quarterly at various locations, primarily in various regions of the United States, but also in Stockholm, Sweden; Toulouse, France; London, England; and Rome, Italy (BKCASE, 2009–2019). The team successfully worked through challenges and differences to produce The Guide to the Systems Engineering Body of Knowledge (SEBoK) wiki and a Graduate Reference Curriculum for Systems Engineering (GRCSE) publication. This article is a collection of personal stories from the team members that focus on overcoming obstacles to successfully produce the final published products.